Relationship between Fisherman's Characteristics and Livelihood Assets with Fisherman's Household Livelihood Strategy - Demi Ilavy Maudi; Trisna Insan Noor; Eliana Wulandari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Pangandaran Regency is one of the new autonomous regions that has potential for fisheries resources in the southern part of West Java, however, the contribution of capture fisheries to GRDP in Pangandaran Regency is still relatively low. The majority of fishermen in Pangandaran Regency, especially in Cijulang District, are traditional fishermen and not all fishermen have the facilities and infrastructure that can support them in catching fish, such as equipment and boats. This research formulates a strategy for fishermen's livelihood to remain sustainable, based on the basic capital which is the potential driver and obstacle in the life of fishermen. The methodology used in this research is a survey with sampling withproportionate stratified random sampling technique. Meanwhile, the formulation of the development model was analyzed using the Structural Equation Model (SEM) with PLS analysis tools. The results showed that most of thefishermen are dominated by fishermen of productive age with the status of fishermen who own boats and fishing gear with more than 30 years of experience as fishermen, andformal education level at the elementary level, but always attends counseling, and has a number of family dependents as many as 2-3 people. In general, the average livelihood assets, namely natural capital (56.14 %), human capital (88.25 %), financial capital (72.59 %), social capital (81.26 %), and physical capital (68 ,78 %). Meanwhile, cumulatively, the highest percentage of household mobility/migration strategies is (71.81%), accumulation (68.97%), survival (60.92%), consolidation (39.68%), and diversification (37.13%). Andthere is a relationship between the characteristics of fishermen and livelihood assets on the livelihood strategies of fishermen.